Is electricity more important than natural gas? Partial liberalization of the Western European energy markets - Kjell Arne Brekke; Rolf Golombek; Sverre A. Kittelsen (University of Oslo, Department of Economics, 2008)
The European Union has introduced directives that aim to liberalize and integrate electricity and gas markets in Western Europe. While progress has been made, particularly in electricity markets, there have been setbacks: for example, because of concerns about national interests and security of supply. Thus it is possible that only part of the energy industry in Western Europe will be liberalized. We use a numerical model to assess what types of liberalization – electricity vs. natural gas; domestic markets vs. international trade – are most influential in decreasing prices and increasing welfare in Western Europe. We find that a partial liberalization of electricity markets has greater quantity and welfare effects than a partial liberalization of gas markets, and that liberalizations of domestic energy markets have (overall) greater effects than liberalizations of trade in energy between Western European countries. Finally, the shortrun effects primarily parallel the long-run effects, though they are significantly smaller.
Keywords: C15; C68; Q40; Q48; 330; energy markets; liberalization; price discrimination; resource rent; Energiemarkt; Elektrizität; Erdgasmarkt; Deregulierung; Preisdifferenzierung; Wohlfahrtseffekt; EU-Staaten